Moderasi Green Perceived Quality pada Pengaruh Green Consumerism dan Value terhadap Revisit Intention Starbucks Kudus - Affan, Hildhan; Supriyanto, Agus (Jurnal Ekonomi dan Bisnis Islam, 2026)
AbstractThis study aims to examine and analyze the influence of green consumerism and green perceived value on revisit intention, as well as the role of green perceived quality as a moderating variable in Starbucks Kudus customers. The study used a quantitative approach with a sample of 100 respondents who had visited at least once. The sampling technique used purposive sampling, while data were collected through a Google Form questionnaire and analyzed using SmartPLS 4. The results showed that green consumerism did not have a positive and significant effect on revisit intention, with a p-value of 0.541 > 0.05. Green perceived value had a positive and significant effect on revisit intention with a p-value of 0.010 < 0.05. Green Perceive Quality was unable to moderate the relationship between Green Consumerism and Revisit Intention with a p-value of 0.116 > 0.05. However, green perceived quality was proven to moderate the relationship between green perceived value and revisit intention with a p-value of 0.040 < 0.05, thus strengthening customer intention to revisit. This study concluded that customers' revisit intentions were more influenced by perceived environmental benefits than by environmental awareness alone. The findings also suggest that perceived green quality plays a significant role in strengthening the influence of green values on customers' revisit decisions.Keywords: Green Consumerism; Green Perceived Value; Green Perceived Quality; Revisit Intention.AbstrakPenelitian ini bertujuan untuk menguji dan menganalisis pengaruh green consumerism dan green perceived value terhadap revisit intention, serta peran green perceived quality sebagai variabel moderasi pada pelanggan Starbucks Kudus. Penelitian menggunakan pendekatan kuantitatif dengan sampel sebanyak 100 responden yang pernah berkunjung minimal satu kali. Teknik pengambilan sampel menggunakan purposive sampling, sedangkan data dikumpulkan melalui kuesioner Google Form dan dianalisis menggunakan SmartPLS 4. Hasil penelitian menunjukkan bahwa green consumerism tidak berpengaruh positif dan signifikan terhadap revisit intention, dengan p-value 0,541 > 0,05. Green perceived value berpengaruh positif dan signifikan terhadap revisit intention dengan p-value 0,010 < 0,05. Green perceived quality tidak mampu memoderasi hubungan antara green consumerism dan revisit intention dengan p-value 0,116 > 0,05. Namun, green perceived quality terbukti mampu memoderasi hubungan antara green perceived value dan revisit intention dengan nilai p-value 0,040 < 0,05, sehingga memperkuat niat pelanggan untuk berkunjung kembali. Penelitian ini menyimpulkan bahwa niat kunjungan ulang pelanggan lebih dipengaruhi oleh nilai manfaat lingkungan yang dirasakan dibandingkan kesadaran lingkungan semata. Temuan ini juga menunjukkan bahwa persepsi kualitas hijau berperan penting dalam memperkuat pengaruh nilai hijau terhadap keputusan pelanggan untuk berkunjung kembali.Kata Kunci: Green Consumerism; Green Perceived Value; Green Perceived Quality; Revisit Intention.